Accretion, radial flows and abundance gradients in spiral galaxies - Pezzulli, G; Fraternali, F (Oxford University Press, 2016)
The metal-poor gas continuously accreting on to the discs of spiral galaxies is unlikely to arrive from the intergalactic medium (IGM) with exactly the same rotation velocity as the galaxy itself and even a small angular momentum mismatch inevitably drives radial gas flows within the disc, with significant consequences to galaxy evolution. Here, we provide some general analytic tools to compute accretion profiles, radial gas flows and abundance gradients in spiral galaxies as a function of the angular momentum of the accreting material. We generalize existing solutions for the decomposition of the gas flows, required to reproduce the structural properties of galaxy discs, into direct accretion from the IGM and a radial mass flux within the disc. We then solve the equation of metallicity evolution in the presence of radial gas flows with a novel method, based on characteristic lines, which greatly reduces the numerical demand on the computation and sheds light on the crucial role of boundary conditions on the abundance profiles predicted by theoretical models. We also discuss how structural and chemical constraints can be combined to disentangle the contributions of inside-out growth and radial flows in the development of abundance gradients in spiral galaxies. Illustrative examples are provided throughout with parameters plausible for the Milky Way. We find that the material accreting on the Milky Way should rotate at 70–80 per cent of the rotational velocity of the disc, in agreement with previous estimates.